Effects of resourcefulness on internet game addiction among college students: The mediating role of anxiety and the moderating role of gender - Zhang, Yan; Zhong, Yun-Ling; Luo, Jing; He, Jin-Long; Lin, Cen; Zauszniewski, Jaclene A.; Zhou, Jin-Hui; Chen, Ying; Wu, Chun-Yan; Wang, Shu-Rui; Li, Zheng-Huan; Tang, Jing; et al. (Frontiers in Public Health, 2023)
The mechanism of internet game addiction are unclear. Whether anxiety mediates between resourcefulness and internet game addiction and whether gender affect its mediation role have not been studied previously. A total of 4889 college students from a college in southwest China were included in this study to complete the investigation, in which three questionnaires were used for evaluation. Pearson's correlation analysis indicated a remarkable negative correlation between resourcefulness with internet game addiction and anxiety, as well as a significant positive correlation between anxiety and this addiction.The structural equation model confirmed the mediation role of anxiety. The multi-group analysis confirmed the moderating role of gender in the mediation model. These findings have advanced the results of existing studies, indicating the buffering effect of resourcefulness on internet game addiction and revealing the potential mechanism of this relationship.